A photocatalytic degradation self-cleaning composite membrane for oil-water separation inspired by light-trapping effect of moth-eye - Li, Zhaoxin; Yin, Liang; Jiang, Shuyue; Chen, Liang; Sang, Shengtian; Zhang, Haifeng (Journal of membrane science, 2023)
Membrane separation technology with superwetting surfaces is ideal for treating water pollution. However, the fouling problem of membranes limits their practical application in this field. Membranes with self-cleaning property during the separation are the key to solve this problem. In this study, inspired by the light-trapping effect of the moth-eye, a kind of composite membrane with efficient self-cleaning by photocatalytic degradation was proposed. The composite membrane is based on polyvinyl alcohol cross-linked tannic acid (PVA-TA) and its photocatalytic function is achieved by doping magnetic titanium dioxide nanoparticles (MTiO2) as well as MXene. Meanwhile, its surface was constructed by magnetically controlled self-assembly method using MTiO2 to mimic the moth-eye structure. The composite membrane has superhydrophilic/underwater superoleophobic, excellent oil-water separation efficiency (99.85%) and long service life (64 cycles). In addition, due to the light-trapping effect of the bionic moth-eye structure and the redox reaction at the interface of MTiO2-MXene composites under sunlight irradiation, the membrane can achieve efficient and convenient photocatalytic degradation self-cleaning by sunlight irradiation. This study will provide new insights into the self-cleaning method of oil-water separation materials. [Display omitted] •Construction of high light absorption efficiency surface by magnetron self-assembly method inspired by the light-trapping effect of moth-eye structure.•Redox reaction occur at the interface of MTiO2 and MXene composite under sunlight irradiation.•The composite membrane shows excellent oil-water separation performance and long service life.•The composite membrane has excellent sunlight-catalyzed degradation self-cleaning property.